2018
DOI: 10.1177/000313481808401005
|View full text |Cite
|
Sign up to set email alerts
|

Advance Directive and Do-Not-Resuscitate Status among Advanced Cancer Patients with Acute Care Surgical Consultation

Abstract: Formal communication of end-of-life preferences is crucial among patients with metastatic cancer. Our objective is to describe the prevalence of advance directives (AD) and do-not-resuscitate (DNR) orders among stage IV cancer patients with acute care surgery consultations, and the associated outcomes. This is a single institution retrospective review over an eight-year period. Two hundred and three patients were identified; mean age was 55.3 ± 11.4 years and 48.8 per cent were male. Fifty (24.6%) patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Similar to prior studies, in this chart review, approximately 15% of patients had an AD on le 8,9 . Over a quarter of the patients were readmitted in the following year.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to prior studies, in this chart review, approximately 15% of patients had an AD on le 8,9 . Over a quarter of the patients were readmitted in the following year.…”
Section: Discussionsupporting
confidence: 84%
“…In one study of intensive care unit patients, 42% of patients had an AD, however the cohort was known to be signi cantly ill, with a mortality of 24% 8 . In contrast, another study examining the prevalence of ADs in a cohort of cancer patients undergoing surgery consultation reported 10% of these patients had a Do-Not-Resuscitate order in their medical record but none had an AD on le 9 . Studies have also demonstrated completion of ADs are associated with lower readmission rates 10,11 , which have implications for both individual patients and health systems.…”
Section: Introductionmentioning
confidence: 95%
“…Cancer types included breast, 42 hematological, 35,33 gynecological, 1,34,48 lung or gastrointestinal, 39 and any type. 23,31,32,[36][37][38]40,41,43,45,46,48,51 Sample sizes ranged from 84 to 2752 participants, with a median of 226 participants per study. Two studies featured fewer than 100 participants.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…36,37,43 No studies examined the impact of out-of-pocket costs on patients. Eighteen studies assessed relationships between EOL discussions and health-care utilization near death 1,23,[32][33][34][35][38][39][40][41][42][43][45][46][47][48]51 and 6 studies assessed place of death. 1,33,35,42,47,51 In addition, 6 studies incorporated elements of time in their assessment of EOL discussions, generally referring to these discussions as early (31þ days before death) or late (within 30 days of death), with later conversations typically occurring in inpatient settings.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation